Development of Molecular Beacon method to detect of JAK2 V617F mutation - Nazemi, Ali (Archives of Advances in Biosciences, 2018)
V617F mutation of JAK2 gene is a point mutation of Somatic cells leading to permanent phosphorylation and protein kinase activity of the JAK2 protein. This mutation is a valuable marker in the diagnosis of myeloid neoplasms. Development of new techniques can be effective and highly sensitive for the detection of the mutation. The aim of this study is designing and executing a molecular beacon probe-based real-time PCR detect to V617F mutation. Test results were reviewed from a set of wild type and cloned JAK2 exon 12 mutated allele genes into plasmid vector and through amplification by Real-Time PCR system. The sensitivity and specificity of Molecular Beacon probes design were tested. The results showed that the Real-Time PCR system has %100 specificity and % 0.001 sensitivity. Based on the results obtained from the molecular beacon probe-based real-time PCR, it was proved that the system is able to detect normal and mutant alleles of JAK2 V617F position with high accuracy and a short time in a closed tube system